The Effect of Gender Equality Perspective Sexual Education on Self-Efficacy as an Effort to Prevent Sexual Violence in Adolescents at SMAN 1 Gorontalo - Desy Sulistiawati Alimudin; Nurdiana Djamaluddin; Nirwanto K. Rahim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Sexual violence is a sexual act that is carried out forcefully and can happen to anyone, including teenagers as a vulnerable group. The lack of gender-based sexual education in schools leads to low knowledge about sexual violence and gender equality, resulting in an impact on self-efficacy and high cases of sexual violence in adolescents. This study aims to determine the influence of sexual education from a gender equality perspective on self-efficacy as an effort to prevent sexual violence in adolescents at SMAN 1 Gorontalo. The study used a quantitative approach with a One Group pre-test and post-test design and involved 65 respondents selected through the Proportionate Stratified Random Sampling technique. The research instrument was in the form of a questionnaire on self-efficacy of sexual violence prevention efforts. The results of the study showed that there were differences before and after being given sexual education from a gender equality perspective about increasing self-efficacy as an effort to prevent sexual violence, the results obtained were In conclusion, there was a significant influence before and after being given sexual education from a gender equality perspective on self-efficacy as an effort to prevent sexual violence in adolescents at SMAN 1 Gorontalo so that it was needed Integrating gender equality-based sexual education in school health promotion programs, health agencies, especially nursing to develop sexual violence prevention programs in the school environment